Pathways From Irrigation to Prosperity, Nutrition and Resilience in Mali - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
The dataset includes information gathered through a face-to-face cross-sectional survey of 1,072 households, of which 444 were irrigating households. The survey was conducted in the Mopti and Sikasso regions of Mali. The survey was a joint collaboration between the International Food Policy Research Institute (IFPRI), the Institut d'Economie Rurale (IER) of Mali, and Texas A&M University (TAMU) and was financially supported by USAID's Bureau for Humanitarian Assistance (BHA) under the Feed the Future "Innovation Lab for Small-Scale Irrigation (ILSSI)." The collected data encompasses a wide range of topics, including household demographics, agricultural production, irrigation practices, water security, water access, sanitation, hygiene, access to rural services and infrastructure, market participation, and nutrition. With such a comprehensive dataset at hand, researchers can delve into analyzing various aspects of the surveyed regions, such as understanding household dynamics, exploring agricultural practices, and assessing the effects of irrigation in different facets of life.